Extension of depth of field using amplitude and phase modulation of the pupil function - Bagheri, Saeed; Javidi, Bahram (Optics letters, 2008)
We analyze the extension of depth of field using both amplitude and phase modulation of the pupil function. In particular, we discuss the advantages and disadvantages of each approach and establish the range of applicability of each method based on the range of spatial frequencies of interest in the imaging system. To the best of our knowledge, this is the first such report on the range of applicability of amplitude and phase modulation to extend the depth of field.